The measurement of labour content: A general approach - Naoki Yoshihara; Roberto Veneziani (Queen Mary University of London, School of Economics and Finance, 2013)
This paper analyses the theoretical issues related to the measurement of labour content in the context of general technologies with heterogeneous labour. A novel axiomatic framework is used in order to formulate the key properties of the notion of labour content and analyse its theoretical foundations. Then, a simple measure of labour content is uniquely characterised, which is consistent with common practice in input-output analysis and with a number of recent approaches in value theory.
Keywords: D57; J24; O33; D46; 330; Labour content; Labour productivity; Technical change; Axiomatic analysis